Derik The Dutch and The Klapertaart and Other Stories: Children’s Picture Book Exploring Racist Bullying - Angelica Livianita Setianto; Stefanny Irawan (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
This paper discusses the process of making children’s picture book with low fantasy as the genre which explore racist bullying among children. The creative work emphasizes on the victims more than the bullies, thus, three stories implement Transactional Theory of Stress and Coping to show how children can cope with the stress of being racially bullied. The main characters in the three stories use problem focused coping, especially planful problem solving to stop the racist bullies from bullying them. The other two stories use Developmental Intergroup Theory to show how children learn prejudices toward other races by learning from the adults around them. The main characters in the last two stories are influenced by the adults around them in developing prejudices against others of different races and bullying them.Keywords: Racist Bullying, Coping Strategy, Transactional Theory of Stress and Coping, Developmental Intergroup Theory, Children’s Picture Books, Low Fantasy.